How the COVID-19 outbreak affected physician-patient relationship - Fakhari, Ali; Dolatkhah, Roya; Dehkharghani, Keivan Fakhari (Journal of Community Medicine and Health Solutions, 2020)
Physician-patient communication is the most basic element and vital skill of physicians in the diagnosis, treatment, and establishing diagnostic protocols. As the risks of contagion and viral infection are higher in physicians and health workers, front line soldiers inpatient care units, so they should establish strict protective measures. However, patients value greatly face to face and close relationships with their doctors, including facial interviews and physical examinations. So social and physical distancing between physician and their patients can be remarked as a bigger toll than the risk of COVID-19 contagious.